Perceived attitudes of the importance and barriers to research amongst Rwandan interns and pediatric residents – a cross-sectional study - Hubert Habineza; Christian Nsanzabaganwa; Naphtal Nyirimanzi; Christian Umuhoza; Katie Cartledge; Craig Conard; Peter Cartledge (BMC Medical Education, 2019)
Abstract Background Globally, interns and residents face significant challenges with respect to research activity. Despite this, they are motivated and have an interest in undertaking research. To date, there has been no research regarding the perceived attitudes towards research activities amongst Rwandan residents and interns. Objectives The primary objective of this study was to describe the perceived attitudes regarding the educational benefits and barriers surrounding research activity amongst interns and residents, and to identify any differences between these groups. The secondary objective was to describe the research methods used by interns and residents in Rwanda. Methods A cross-sectional descriptive study of interns and pediatric trainees at the University of Rwanda. An online questionnaire using Likert scale questions was sent electronically to eligible participants. Results A total of sixty participants (38 interns and 22 pediatric residents) responded to the survey. Both groups acknowledged the educational importance of undertaking research, with interns reporting this more than residents. Both groups identified the following as barriers to research: faculty lacking time to mentor, lack of funding, lack of statistical support, and lack of faculty experienced in conducting research. Interns (87%) were much more likely to have undertaken retrospective research than pediatric residents (14%). Few interns or residents submitted their research for publication (27%). Conclusions Both interns and residents understood the importance of research, but many barriers exist. Increasing the time available for experienced faculty members to supervise research is challenging due to low faculty numbers. Novel solutions will need to be found as well as expanding the time for trainees to perform research.